Simulation and Design of LiNbO $_{3}$ Modulators With Switched Segmented Electrode Structure for High Bandwidth and Low Half-Wave Voltage - Hao Chen; Huangfan Wang; Feiwan Xie; Shaohua Yang; Huafeng Dong; Fugen Wu; Wenyuan Liao (IEEE Photonics Journal)
A lithium niobate thin-film(LNTF) electro-optic modulator(EOM) with segmented electrode structure is investigated, and the influence of the modulator's structural configuration on its performance is achieved. In contrast to conventional couplers, the design incorporates a 2 × 2 S-shaped directional coupler. Our modulator achieves a bandwidth of nearly 110 GHz and a half-wave voltage of 1.45 V $·$ cm. A comparative analysis between two configurations: one with SiO $_{2}$ cladding covering the entire surface and the other with coverage limited to the electrode gaps, which reveals the latter potential for enhancing device performance. The accuracy of the simulation results is substantiated through both software analysis and theoretical calculations. The simulation results provide valuable insights for the design of LNTF EOM, highlighting the efficacy of the proposed segmented electrode structure.